Analisis Yuridis terhadap Perlindungan Hukum Investasi Asing di Indonesia setelah Lahirnya Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja - Porman Hutabarat; Markoni Markoni (Jurnal Syntax Admiration, 2022)
Investment is one of the important factors in the development of a country. The state is required to regulate as well as possible so that investment grows and has a positive impact on society. The investment licensing process, which should be quick and easy, turns out to be convoluted, ineffective and inefficient both in terms of time and high costs. The government is trying to attract foreign investment by reforming the ease of doing business by revamping regulations that are considered to make it difficult for investors to attend. The Job Creation Law is one of the legal breakthroughs to simplify various laws. Using the Omnibus Law method, 78 laws have been revised to become one Job Creation Law which regulates multi-sectors which are divided into 11 clusters, namely: simplification of permits, investment requirements, employment, land acquisition, ease of doing business, research and innovation support, government administration , imposition of sanctions, facilitating the empowerment and protection of MSMEs, investment and government projects, and economic zones. The Job Creation Law is useful for improving the investment climate and realizing legal protection in encouraging investment to accelerate economic transformation, align central and regional policies, provide ease of doing business, overcome overlapping regulatory problems and eliminate sectoral egos. This research is a descriptive analysis carried out using a normative juridical approach, the research material is literature or document studies carried out on statutory regulations. Based on the research results, it is known that the Job Creation Law and its implementing regulations create synchronization and collaboration with simplified regulations to facilitate the investment process. Investors receive legal protection and investment realization grows positively.